Computational Fluid Dynamic Analysis on Double-Type Drying Machine Design - Waleed Waleed; Mona Nur Moulia; Athoillah Azadi (EPI International Journal of Engineering, 2025)
The design of a double-type dryer with tray and rotary will be designed to be able to dry chips and grains commodities in one time process for energy and time-saving. In the designing process, Computational Fluid Dynamic (CFD) simulation is used to analyze the distribution of hot air and minimize failures in the design. The purpose of this study was to determine the pattern of hot air flow distribution and determine the best design of the drying machine. The parameters used in the CFD input have a temperature of 60 oC, air velocity 1 m/s, and a pressure 1.01325 bar with a constant time. This study used 2 treatments, namely the outlet position parameter (A) with dimension 60 mm x 60 mm and the number of holes in the bulkhead between the tray and rotary have the gap type (L) with dimension 540 mm x 70 mm with a total of 21 treatments. This research begins with pre-processing for made geometry and boundary condition input, next is solver process with average iterations 298 with 36 s interval, and the last is post-processing for having air contour. The results showed that the best treatment based on temperature pattern is the A2L1L2 treatment, with the output A2 and 2 limiting gaps, on gaps 1 and 2. This treatment had an average temperature distribution of 56.69 oC, deviation 3,55 oC, air velocity 1.57 m/s, and turbulence 0.021 m/s.